تطوير نموذج لأمثلة توزيع موارد العمال في مشاريع التشييد - جراد فايز; مكية سماح; أحمد علي (Latakia University Journal -Engineering Sciences Series, 2019)
Resource allocation optimization is one of the challenging problems in project management in today’s economy because of the complexity of projects and the increasing costs of the resources in construction projects. This research presents the definition of the importance of smoothing project resources and its role in increasing the quality of achieving projects. Since there is no software model to smooth the project resources for reaching the optimum allocation, this research aims to develop an optimization model for resource smoothing according to the proposed constraints, which in turn reduces the fluctuations in resource usage diagram without any change in the project duration. The proposed model utilizes a system that depends on the experiential method to find the best solution, and the value of has been used as a helpful criterion to calculate the measure of the fluctuations in daily resource demands. After formulating the proposed model, it is programmed using DEV program, which uses C++ language to find the optimum solution. At last, an illustrative example is presented to ensure the proposed model, and the application results come identical with research objectives. A comparison with the results of the feature of “resource leveling” in the known construction management programs showed a high efficiency of the developed model. The results of the developed model met the intended goal of achieving the best schedule with the minimum cumulative resource fluctuations. تعد عملية توزيع الموارد إحدى المشكلات الصعبة في إدارة المشاريع في اقتصاد اليوم، وذلك بسبب تعقيد المشاريع وبسبب التكاليف المتزايدة للموارد في مشاريع التشييد. سيتم في هذا البحث التعريف بأهمية صقل موارد المشروع ودورها في رفع جودة انجاز المشاريع. وبما أنه لا يوجد نموذج برمجي لصقل موارد المشروع والوصول بها إلى التوزيع الأمثل، يهدف هذا البحث إلى تطوير نموذج أمثل لصقل الموارد وفقاً للمقيدات المفروضة، والذي يقلل بدوره من التقلبات في مخطط استخدام المورد من دون أي تغيير في مدة المشروع. يستخدم النموذج المقترح نظاماً يعتمد على المنهج التجريبي لإيجاد الحل الأفضل، وتم استخدام قيمة كمعيار مساعد لحساب مقدار التقلبات في احتياجات المورد اليومية. بعد صياغة النموذج المقترح تمت برمجته باستخدام برنامج DEV، والذي يستخدم لغة C++ لإيجاد الحل الأمثل. في النهاية تم تقديم مثال توضيحي للتأكد من صحة النموذج المقترح، وجاءت نتائج التطبيق متطابقة مع أهداف البحث. وأظهرت المقارنة مع نتائج خاصية "تسوية الموارد" في برامج إدارة التشييد المعروفة كفاءة عالية في النموذج المطور. حققت نتائج النموذج المطور الهدف المنشود وهو تحقيق أفضل جدول زمني بأقل قدر ممكن من تقلبات الموارد التراكمية.